Pemberian Kotoran Jangkrik dan ZPT Organik untuk Meningkatkan Pertumbuhan dan Produksi Jagung Manis (Zea mays L. saccharata). - Eni Sukesih; Nuraida Nuraida; Iwan Hasrizart (Jurnal Agrofolium, 2023)
The purpose of this research was to examine the growth and yield of sweet corn (Zea mays L. saccharata) in response to the application of Cricket Manure and Organic ZPT, as well as the interaction between these two factors. There were two factors and three replications in this randomized factorial block design experiment: the first component, provision of cricket droppings (J), had 4 levels, namely J0 = no treatment (control), J1 = 1.5 kg/plot, J2 = 3 kg/plot and J3 = 4.5 kg/plot. The second factor of giving organic ZPT (Z) consisted of 3 levels, namely Z0 = no treatment (control), Z1 = 3 cc/liter of water/plot, and Z2 = 6 cc/liter of water/plot. Plant height (cm), cob husk length (cm), and cob weight (g) were measured in each plot. The application of cricket dung greatly changed the parameter of cob weight per plot, significantly affected the parameter of cob length, and had no significant effect on the parameter of plant height. The administration of organic ZPT had no discernible impact on any of the measured variables, and neither did the addition of cricket poop.